Upregulation of interferon gamma gene expression among asymptomatic malaria adults in Bayelsa State, Nigeria - Faith Ajiebabhio Ogbole; Chidi Uzoma Igwe; Chinyere Henrietta Onuoha; Chiamaka Perpetua Nzebude; Hilary Izuchukwu Okagbue (Scientific African)
Despite concerted efforts, malaria remains a global public health problem. Treatment for asymptomatic malaria will reduce the health care burden of malaria. However evidence-based data for the presence of systemic pathology in asymptomatic malaria, which might inform treatment remains limited. The present study investigated the current prevalence of asymptomatic malaria in Bayelsa State, Nigeria and differences in interferon gamma (IFNγ) mRNA expression between asymptomatic malaria individuals (AMIs) and uninfected individuals (UIs), in relation to ABO blood groups and hemoglobin genotype (Hb) variants. A cross-sectional design was employed to randomly select 146 non-febrile participants from Sagbama LGA, Bayelsa State. Plasmodium falciparum infection was determined using high-resolution melting analysis and participants were grouped into UIs and AMIs. Hb, blood groups, and IFNγ mRNA expression were determined using electrophoresis, agglutination, and real-time PCR method respectively. Logistic regression and t-test were used to determine significant differences between groups at p < 0.05. The current prevalence of asymptomatic malaria in Bayelsa State was found to be 89.73 %. Age and sex were associated with asymptomatic malaria (p < 0.05). Plasmodium falciparum DNA melt curves for AMIs aligned at 83.89 ± 0.34 °C, while the amplification cycle thresholds were below 30 cycles. Compared with UIs, the gene expression of IFNγ mRNA was significantly (p < 0.001) higher among AMIs. Also, among AMIs those with A, B, and AB blood groups expressed significantly higher levels of IFNγ mRNA compared with blood groups O AMIs. Furthermore, AMIs with HbAA expressed significantly higher levels of IFNγ mRNA compared with HbAS AMIs. The novelty of the present study is the demonstration of the existence of systemic pathology in asymptomatic malaria and the demonstration that the intensity of systemic pathology is dependent on blood types and haemoglobin genotype variants. Findings of the present study have implications for policy creation towards asymptomatic malaria treatment.